The meaning of education after Abu Ghraib: revisiting Adorno’s politics of education - Giroux, Henry A. (FCL-UNESP Laboratório Editorial, 2010)
How might education be used to question the common sense of the war on terrorism or to rouse citizens to challenge the social, political, and cultural conditions that led to the horrible events of Abu Ghraib? Just as crucially, we must ponder the limits of education. Is there a point where extreme conditions shortcircuit our moral instincts and ability to think and act rationally? If this is the case, what responsibility do we have to challenge the reckless violence-as-fi rst-resort ethos of the Bush administration? Such questions extend beyond the events of Abu Ghraib, but, at the same time, Abu Ghraib provides an opportunity to connect the sadistic treatment of Iraqi prisoners to the task of redefi ning pedagogy as an ethical practice, the sites in which pedagogy takes place, and the consequences of pedagogy to rethinking the meaning of politics in the twenty-fi rst century. In order to confront the pedagogical and political challenges arising from the reality of Abu Ghraib, I want to revisit a classic essay by Theodor Adorno in which he tries to grapple with the relationship between education and morality in light of the horrors of Auschwitz.